Developing English Materials for Nursing Students of SMK Kesehatan Bali Medika Denpasar - Pratama Putra, I G. Aris (Jurnal Pendidikan Bahasa Inggris Indonesia, 2019)
This study aimed at: a) analysing materials needed for nursing students of SMK Kesehatan Bali Medika Denpasar; b) developing materials for teaching English for nursing students of SMK Kesehatan Bali Medika Denpasar; c) analysing the quality of the developed materials for teaching English for nursing students of SMK Kesehatan Bali Medika Denpasar as perceived by expert judges. This study used R & D model proposed by Sugiyono (2013). Step 1 (identifying the potency & problem phase or need analysis phase) of Sugiyono Model of R&D Design used Hutchinson & Waters’s Learning-Centered Need Analysis Framework (1987) in order to be used to analyze target and learning needs of English for nursing students. The present study was limited into developing the product and expert judgment. Therefore, the field test was not conducted in the present study. The materials for nursing students of SMK kesehatan bali medika Denpasar  were developed based on  R and D suggested by sugiono (2013) and every unit of developed materials are presented based on the model of ESP material design of Hutchinson and Waters (1987:108) which consisted of input, content focus, language focus, and task. The findings of this study showed that there were 8 units of English for nursing students’ material had been developed. Those were; (1) Introduction; (2) Giving Directions in Hospital; (3) Health Problems; 4) Types of Symptoms; 5) Diagnosing Patient’s Problems; 6) Discussing Observation; (7) Assessment; (8) Patient Assessment. The materials were focused on developing the students’ speaking ability. The quality of the product very good (Product Quality = 4.13) and had met the criteria of material